Through Highways: Construction of the Expressway System in Milwaukee County, 1946-1977 - (:unkn) unknown (My University, 2015)
This thesis traces the route selection and planning of the Interstate Highway System in Milwaukee County and places it within a larger national context. It asks why Milwaukee's expressways were built along their eventual routes and why certain routes were cancelled. The thesis finds that a combination of transportation studies, compromise between units of government, and the availability of funding—especially federal funding—most contributed to route selection, while decisions at the county and state level to cancel specific expressway segments came after citizen opposition and political pressure. The need for a major system of express highways, wide boulevards or avenues, or similar major roads in Milwaukee dated to the 1920s. Immediately after World War II, demand for a solution to growing traffic congestion in the downtown area and surrounding neighborhoods mounted. Mayors John Bohn and Frank Zeidler, Land Commissioner Elmer Krieger, and other officials to begin planning for a city-wide system of controlled access, divided express highways to move traffic across the city and into and out of the downtown area more effectively. Within a few years, overwhelming costs and limited intergovernmental cooperation compelled Milwaukee to agree to shift oversight to Milwaukee County. Under the new organizational structure, an appointed Milwaukee County Expressway Commission planned the expressway system and worked out details regarding route selection and highway construction, but the Milwaukee County Board retained fiscal control. Municipal governments were also allowed to formally object to route proposals, with the State Highway Commission serving as an intermediary in the event of disagreements between municipal governments and the Expressway Commission. After the passage of the Interstate Highway Act in 1956, additional federal funds became available for highway construction, prompting County officials to ask the federal government to designate several highway routes in Milwaukee County as interstate highways. Public opinion generally favored the expressways in the 1940s and throughout the 1950s, but by the mid-1960s, support diminished. Expressway construction in older, densely populated neighborhoods brought the demolition of homes, businesses, and churches, and displaced thousands. Little or no relocation assistance was available before 1968. An anti-freeway movement opposed to additional construction began in 1967 and within a few years, won several political and public relations victories. A court ruling in 1972 halted a proposal to construct an expressway parallel to Lincoln Memorial Drive near the shore of Lake Michigan. The Milwaukee County Expressway Commission cancelled other routes in the 1970s. Afterward, expressway construction largely ended until 1999.
Keywords: Expressways; Freeways; Interstates; Milwaukee; Rapid Transit; Socialists